Resources Approach as a New Paradigm in Stratification Studies - Наталья Евгеньевна Тихонова (Journal of Economic Sociology, 2010)
The author analyses the possibility of social structure analysis of contemporary Russian society with the help of resource approach – new scientific conception developing within the last thirty years. The basis for stratification in this approach is the volume and structure of resources (capitals and actives), that people have and which are not the only traditional economic capital but also human and authority capitals as well. Special attention is given here to the types of resources obtained from the socialization, culture and behavioral models, which were considered earlier as the consequences of economic status as well as physiological status.  According to the author the transition to the resources concept as the basis for the stratification theory is supported by the previous development of the stratification theories in the world and is promising the methodological jump up from the current stagnating stratification theories.